3D buckling variable poisson module auxetic membranes - Mohamed Firdaus Mohamed Shaik Abdul Kader Maricar (2019)
Auxetics are a branch of meta-materials which have been researched over the past few decades and continue to garner interest, especially with modern manufacturing methods, which allow for the rapid and accurate production of these structures. For the scope of this project, it was chosen to focus on 2-dimensional (2-D) auxetic membranes with re-entrant honeycomb cells. This report focuses on the 3-dimensional (3-D) buckling of stressed auxetic membranes with varying Poisson’s ratio. A method to design auxetic membranes with varying Poisson module with respect to an arbitrary function was developed. Some membranes were also fabricated using 3-D printing and stretched to observe out of-plane deflection. The design process of the membranes, which involves the use of OpenScad, a script-based modelling software, is elaborated in further detail. Auxetics show great potential in numerous real world applications and from the findings of this project, there are many possibilities to further research the effects of varying the Poisson’s ratio of membranes with various cell geometries to achieve desired controllable deformations.